High entropy silicides: CALPHAD-guided prediction and thin film fabrication. (August 2021) - Vyatskikh, Alexandra L.; MacDonald, Benjamin E.; Dupuy, Alexander D.; Lavernia, Enrique J.; Schoenung, Julie M.; Hahn, Horst
Abstract: The field of high entropy materials provides a vast, multicomponent compositional space, where scientifically interesting and technologically important materials with novel properties can be identified. Recently, the design methodologies that are traditionally used for high entropy alloys have been extended to silicide materials, which are particularly promising due to their potential applications in microelectronics. In this study, the CALculation of PHAse Diagrams (CALPHAD) approach was used to identify two candidate single-phase high entropy silicides (HES): the ternary (CrMoTa)Si2 and the quinary (CrMoTaVNb)Si2 . Both candidate compositions were experimentally synthesized via electron beam evaporation followed by heat treatment in vacuum, which facilitated the solid-state reaction. Both the ternary (CrMoTa)Si2 and the quinary (CrMoTaVNb)Si2 HES formed a single phase with a C40 hexagonal crystal structure, validating our CALPHAD phase formation predictions. This work reports the first experimental realization of a thin film high entropy silicide material. Graphical abstract: Image, graphical abstract